Web-Based and Mobile Suicide Prevention Interventions for Young People: A Systematic Review - Perry, Yael (J Can Acad Child Adolesc Psychiatry, 2016)
OBJECTIVE: Suicide is a significant public health issue, and is especially concerning in adolescents and young adults, who are over-represented both in attempts and completed suicide. Emerging technologies represent a promising new approach to deliver suicide prevention interventions to these populations. The current systematic review aims to identify online and mobile psychosocial suicide prevention interventions for young people, and evaluate the effectiveness of these interventions. METHOD: PsycINFO, Medline, Embase and The Cochrane Library were electronically searched for all articles published between January, 2000 and May, 2015. Peer-reviewed journal articles reporting on interventions for young people aged 12–25 years with suicidality as a primary outcome were eligible for inclusion. No exclusions were placed on study design. RESULTS: One study met inclusion criteria, and found significant reductions in the primary outcome of suicidal ideation, as well as depression and hopelessness. Two relevant protocol papers of studies currently underway were also identified. CONCLUSIONS: There is a paucity of current evidence for online and mobile interventions for suicide prevention in youth. More high quality empirical evidence is required to determine the effectiveness of these novel approaches to improving suicide outcomes in young people.